Why the biomedical Sciences need Philosophy: theoretical and practical Reasons illustrated with examples from the BioThera Institute of Philosophy - Bianchini, Alahi Dana (2021)
The biomedical sciences need philosophy on at least two levels. Firstly, we can find strong arguments that recognize the need for philosophy on a theoretical level, such as the development of scientific theories that in turn can have effects such as the development of new treatments or other medical interventions. However, philosophy, and particularly bioethics, is necessary for the biomedical sciences at the practical level, that is, in the daily practice of science and the achievement of its goals and results. In this work, we will reconstruct some of the arguments that point out the importance of philosophy for science on a theoretical level, and, furthermore, we will argue that these same conceptual tools of philosophy can be useful on a practical level of biomedical sciences too. To this end, we will present four cases from the conceptual research conducted by the BioThera Institute of Philosophy: the enhanced definition of medical innovation as a new non-validated practice, the ethical justification of the duty of States to promote clinical research, the fair play model for the distribution of fair benefits in clinical research, and the ethical model for allocation of extremely scarce resources in times of public health emergency.